A scorched earth: The fate of the Bulgarian economic background during the expedition of Nikephoros I Genikos of 811 - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2020)
The article is dedicated to the impact of the military expedition led by the Byzantine emperor Nikephoros I Genikos (802–811) on the overall political and economic situation of the Bulgarian state. During the military operations carried out in the Khanate, the Byzantine forces undertook the devastation of arable fields, the killing of farm animals and probably committed murders of the local population. Many researchers associate this activity with the loosening of discipline within the army, which was to be the result of a lack of control on the part of the commander-in-chief. On the basis of the correlation and rationalization of the sources in the matter, we have to interpret all these actions in a completely different way, as a conscious activity aimed at causing the Bulgarians the greatest possible losses by the imperial army. Moreover, the interpretation contradicts the universally accepted thesis, that the imperial campaign was aimed at eliminating Bulgarian statehood and incorporating its lands into Byzantium. It seems, therefore, that the purpose of the described activities was to exclude, for a long time, Khan Kroum (796/803–814) and his subordinates from military engagement in Thrace, Macedonia, i.e. areas where the Empire tried to regain and consolidate its influence.